Muslims’ Market and the Lawfulness Purity of Its Goods - Muhammad Imami; Muhammad Hasan Haeri (آموزه‌‌های فقه مدني)
Market provides much of the needs of man. In the one hand, Islam has regarded some conditions for using some goods that sometimes its obtaining is not so easy and the believer becomes uncertain about its using. Defining the market and stating the subject of this article, it propounds generally the universal rule of genuine permitting of the creatures and then considers the necessity of lightening of legal slaughter of animals and their products, market rule, the situation of the non-Muslims’ goods and imported goods.